An Exploration of Morpho-Syntactic Elements of Block Language in Journalistic Discourse - Yaseen, Omar Hazim (Journal of Humanities & Social Sciences, 2025)
This study aims to explore the morphological and syntactic elements that characterise what is known as "block language" in journalistic discourse through a comparative analysis of Arabic and English texts. The study adopted a mixed qualitative-quantitative methodology, and the sample comprised 100 texts (50 Arabic texts from Al-Quds Al-Arabi and 50 English texts from The Guardian).The results showed that nominal constructions are the most prevalent, accounting for 88% of Arabic texts and 82% of English texts. This is followed by grammatical ellipsis, accounting for 76% of Arabic texts and 70% of English texts. The passive voice is then used, accounting for 58% of Arabic texts and 72% of English texts. The study also showed that Arabic texts tend to use more ellipsis and syntactic reduction, while the passive voice is more prominent in English. It turns out that block language is not just a stylistic choice, but a functional strategy aimed at brevity, displaying apparent neutrality, formulating ideological positions, and sometimes concealing the agent or responsibility.”The study recommends continuing research into the ideological dimensions of block language across various media genres, and the need to integrate the analysis of morphological and syntactic phenomena into journalism and translation curricula, thus contributing to the development of critical awareness and analytical reading skills of media texts.
Keywords: Block Language; Journalistic Discourse; Functional Grammar; Media Linguistic Interaction